Utility Of A Smartphone In Assessment Of Retinal Manifestations In Patients With Diabetes Mellitus In Chengalpattu District - Ananthappan, Keshav; K, Murugan (Journal of Neonatal Surgery, 2025)
Aim:The aim of the study is to assess the sensitivity and specificity of smartphone-based fundus imaging as a screening tool for the detection and grading of diabetic retinopathy (DR), in comparison to the standard digital retinal photography. MethodsA total of 144 individuals (288 eyes) with type 2 diabetes underwent standard seven-field digital fundus imaging using both a Canon fundus camera and the indigenous smartphone-based fundus imaging at a tertiary care center in South India. Diabetic retinopathy (DR) grading was independently conducted employing the modified Early Treatment Diabetic Retinopathy Study (ETDRS) classification system. Sight-threatening diabetic retinopathy (STDR) was defined as the presence of either proliferative DR (PDR) or diabetic macular edema (DME). Sensitivity, specificity, and image quality of the imaging modalities were evaluated. ResultsThe mean age of the participants was 53.5 ±9.6 years and mean duration of diabetes 12.5±7.3 years. The Fundus camera showed that 43.9% had non-proliferative DR(NPDR) and 15.3% had PDR while the smartphone-based fundus imaging showed that 40.2% had NPDR and 15.3% had PDR. The sensitivity and specificity for detecting any DR by smartphone-based fundus imaging was 92.7% (95%CI 87.8–96.1) and 98.4% (95%CI 94.3–99.8) respectively and the kappa (ĸ) agreement was 0.90 (95%CI-0.85–0.95 p<0.001) while for STDR, the sensitivity was 87.9% (95%CI 83.2–92.9), specificity 94.9% (95%CI 89.7–98.2) and ĸ agreement was 0.80 (95%CI 0.71–0.89 p<0.001), compared to conventional photography. Conclusion:Smartphone-based fundus imaging is effective for screening and diagnosis of DR and STDR with high sensitivity and specificity and has substantial agreement with conventional retinal photography..